The regulation of glucose and lipid homeostasis via PLTP as a mediator of BAT–liver communication. (16th July 2020) - Sponton, Carlos H; Hosono, Takashi; Taura, Junki; Jedrychowski, Mark P; Yoneshiro, Takeshi; Wang, Qiang; Takahashi, Makoto; Matsui, Yumi; Ikeda, Kenji; Oguri, Yasuo; Tajima, Kazuki; Shinoda, Kosaku; et al.
Abstract: While brown adipose tissue (BAT) is well‐recognized for its ability to dissipate energy in the form of heat, recent studies suggest multifaced roles of BAT in the regulation of glucose and lipid homeostasis beyond stimulating thermogenesis. One of the functions involves interorgan communication with metabolic organs, such as the liver, through BAT‐derived secretory factors, a.k.a., batokine. However, the identity and the roles of such mediators remain insufficiently understood. Here, we employed proteomics and transcriptomics in human thermogenic adipocytes and identified previously unappreciated batokines, including phospholipid transfer protein (PLTP). We found that increased circulating levels of PLTP, via systemic or BAT‐specific overexpression, significantly improve glucose tolerance and insulin sensitivity, increased energy expenditure, and decrease the circulating levels of cholesterol, phospholipids, and sphingolipids. Such changes were accompanied by increased bile acids in the circulation, which in turn enhances glucose uptake and thermogenesis in BAT. Our data suggest that PLTP is a batokine that contributes to the regulation of systemic glucose and lipid homeostasis as a mediator of BAT‐liver interorgan communication. Synopsis: Phospholipid transfer protein (PLTP) released from BAT controls energy expenditure and systemic glucose/lipid homeostasis. The metabolic benefit of PLTP is mediated through a BAT‐liver interorgan communication that involves the regulation of lipoproteins and bile acids. BAT secretes PLTP as a "batokine". PLTP increases the reverse transport of cholesterol to the liver, thereby stimulating the release of primary bile acids that activate BAT thermogenesis. Increased PLTP mitigates diet‐induced obesity, glucose intolerance, and dyslipidemia in mice. Abstract : Phospholipid transfer protein (PLTP) released from BAT controls energy expenditure and systemic glucose/lipid homeostasis. The metabolic benefit of PLTP is mediated through a BAT‐liver interorgan communication that involves the regulation of lipoproteins and bile acids.